Juridical Analysis of The Position of Adopted Children and Procedures for Adopting Children by Single Parents in Indonesia - Pristina Al Jawi Putri; Taufiq Nugroho (Universitas Muhammadiyah Surakarta, 2024)
Adopted children and the process of adopting children by single parents are examined from a legal perspective in this article. The research methodology takes a normative legal stance by reviewing relevant laws and court decisions. With an emphasis on the differences and recent changes in the applicable legal requirements, this article provides a thorough understanding of the situation of adopted children and single parent adoption procedures. The legal consequences, processes, and rights of adopted children, including adopted children adopted by single parent s, are discussed in this paper. In response to the issue statement, key points are raised. The findings of this study highlight the adequate protection of children adopted by single parents and the reform of the child adoption system.